AB1345 The number needed to offend: Beliefs and feelings in patients and rheumatologists. (23rd January 2014) - Padilla-Ibarra, J.; Sandoval-Castro, C.; Aguilar-Lozano, L.; Castillo-Ortiz, D.; Pacheco-Lorenzo, R.; Gonzalez-Leija, M.; Duran-Barragan, S.; Russell, A.S.; Davis, P.; Ramos-Remus, C.
Abstract : Background: Beliefs and emotions drive behavior. Rheumatologists face a broad range of disorders, and delivering related information can be conflicting to patients' believes and thus evoke offensive emotions; in addition, rheumatologists may have feelings associated with diagnoses and project them with consequences in doctor-patient relationship. Objectives: A) To explore connotations and potential offensiveness of 10 different mechanistic labels for rheumatic symptoms in new referred patients with musculoskeletal complaints. B) To explore the potential offensiveness of 10 different mechanistic scenarios in Mexican and Canadian rheumatologists. Methods: A) Consecutive patients attending for the first time at rheumatology outpatient clinic in México were interviewed (structured format) before they saw the rheumatologist. Patients were asked about feelings provoked (i.e. angry, hopeful, etc.) if the rheumatologist gave them one out of ten different mechanistic labels (i.e. stress, autoimmunity, etc.); the rheumatologist was asked then for a medical diagnosis. B) Canadian and Mexican rheumatologists were invited to answer an internet based structured questionnaire about the feelings they may have at the moment they identify each of the 10 different provided scenarios. The "offensive score" was calculated as the proportion of individuals who endorsed offensive feelings, as per protocol definitions; then, a "number needed to offend" (NNO) was calculated assuming an ideal world in which no one is ever offended and using standard estimates for number needed to harm. Results: 150 patients were included, 78% were females, the mean age ± SD was 49±15 yr and formal education 9.5±4 yr. Overall, inheritance, degenerative and inflammatory labels had fewest negative connotations (NNO 16, 12 and 13, respectively), and psychological, functional, and "idiopathic" the most (NNO 3, 3 and 2). Recoding mechanistic labels into "organic" and "functional" the differences were significant (NNO 9 and 3). Stratification by rheumatic diagnosis, patients with inflammatory systemic diseases expressed more negative connotations with functional, "idiopathic" and "not sleeping well" labels (NNO 3 for each). Patients with diseases such as fibromyalgia accepted better autoimmune, inherited disease or inflammatory labels (NNO 17, 9 and 18, respectively) than psychological, functional and "idiopathic" labels (NNO 2, 3 and 1). By other hand, 186 Mexican rheumatologists (36% response rate) and 71 Canadian rheumatologists (23% response rate) answered the questionnaire. Overall, inflammatory and autoimmune labels had the fewest negative connotations (NNO 90 for both), and idiopathic and somatization the most (NNO 2 and 3). Recoding diagnosis labels into "organic" and "functional" the differences in the NNO were notable (51 and 4 for Mexicans and 47 and 5 for Canadians). No other significant differences were observed between Mexican and Canadian rheumatologist. Conclusions: Receiving or giving mechanistic/explanatory labels clearly produce feelings and carries a risk to offend. In this study the NNO in patients and rheumatologists went from 1 to 90. Rheumatologists should seek better ways to deliver accurate information, avoiding idiopathic, functional and psychological labels. Disclosure of Interest: None Declared